2021
DOI: 10.3390/ijerph18052566
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Evaluation of Parent-Assisted Children’s Friendship Training to Improve Social Skills and Friendship Quality in Children with Autism in Malaysia

Abstract: Background: This study evaluates the effectiveness of parent-assisted children’s friendship training intervention for enhancing friendship quality and social skills among children with autism spectrum disorders (ASD). We conducted a quasi-experimental study to investigate the effective outcomes of social skills and friendship quality in the pre-and post-parent-assisted CFT intervention phases; Methods: to conduct a 12-week field session, 30 children with their parents were selected. The Social Skills Improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…This study is part of a larger mixed-methods study that investigates the impact of the CFT on social skills among children with ASD conducted by [ 11 ]. This larger study has indicated improved social skills and friendship quality after participating in CFT [ 11 ]. The qualitative phase of this larger study is the current focus of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger mixed-methods study that investigates the impact of the CFT on social skills among children with ASD conducted by [ 11 ]. This larger study has indicated improved social skills and friendship quality after participating in CFT [ 11 ]. The qualitative phase of this larger study is the current focus of this study.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, previous studies have only focused on the effectiveness of CFT without exploring it from the parent’s perspective. Furthermore, parental relationship closeness is mentioned as the main parameter that influences the success of CFT [ 11 ]. Many children have been diagnosed with ASD, yet there are limited resources available for their families, especially parents, who need to care for their children with special needs.…”
Section: Introductionmentioning
confidence: 99%
“…Others have focused on parents’ own support needs while caring for an autistic child ( Derguy et al, 2015 ; Dieleman et al, 2018 ). Only a few studies have documented parents’ experiences within specific treatment programs autistic for children ( Choque Olsson et al, 2016 ; Ong et al, 2021 ; Stadnick et al, 2013 ; Stahmer et al, 2017 ). These studies broadly focus on evaluating feasibility for parents, positive outcomes, and identifying helpful components, such as use of active parent coaching ( Stadnick et al, 2013 ; Stahmer et al, 2017 ).…”
mentioning
confidence: 99%
“…These studies broadly focus on evaluating feasibility for parents, positive outcomes, and identifying helpful components, such as use of active parent coaching ( Stadnick et al, 2013 ; Stahmer et al, 2017 ). With respect to group-based SST programs for children and adolescents, the limited qualitative studies describe parent satisfaction with treatment, with parents reflecting on positive changes in their child’s social skills and confidence ( Choque Olsson et al, 2016 ) and on their own awareness and learning through the program ( Ong et al, 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation